T100 mGT converted into mHAT for domestic applications: Economic analysis based on hourly demand. (15th February 2016) - Montero Carrero, Marina; De Paepe, Ward; Parente, Alessandro; Contino, Francesco
Highlights: We analyse the economics of an mGT working as a CHP unit and as an mHAT. We consider hourly heat and electricity demand profiles and 25 price scenarios. We assess the feasibility of the projects with the NPV, IRR and discounted cash flows. CHP and mHAT are economically viable for high electricity and low natural gas prices. If investing in CHP is feasible, it is worth transforming the unit into an mHAT. Abstract: Micro Gas Turbines (mGTs) appear as a promising technology for small-scale (up to 500 kW) Combined Heat and Power (CHP) production. However, their rather low electrical efficiency limits their profitability when the heat demand is low. Hot liquid water injection in mGTs—by means of a saturation tower within the micro Humid Air Turbine (mHAT) cycle—allows both improving the flexibility of heat production and the electrical efficiency of mGTs; two qualities that if enhanced would result in an increased economic feasibility of the technology. Based on simulations performed on a Turbec T100 mGT converted into an mHAT, this paper presents an assessment of the economic profitability of both an mGT (working as a CHP) and an mHAT unit operated in real network conditions. To that end, we have used net present value, internal rate of return and discounted cash flow stream methodologies. The input to the study consists of (1) hourly heat and electricity demand profiles of two distinctive users, one located in Brussels the other in San Francisco and (2) 25 electricity and natural gas price scenarios. Our aim is to investigate whether the increase in flexibility and electrical efficiency achieved when transforming an mGT into an mHAT offsets the additional costs. Results show that in scenarios with high electricity and low natural gas prices—the relationship between these two variables depending on the user, CHP and mHAT units are economically competitive. For all the price combinations where investing in mGT technology is feasible, it is worth transforming the unit into an mHAT. Moreover, the lower the electricity demand with respect to the nominal T100 production (100 kWe ), the more sensitive the user is to the price at which electricity is sold to the grid and therefore, the more the feasibility of mGT and mHAT technologies depends on subsidies or primes on surplus-electricity production.